Hydrodynamic effects of biofouling-induced surface roughness – Review and research gaps for shallow water offshore wind energy structures. (15th March 2023) - Maduka, Maduka; Schoefs, Franck; Thiagarajan, Krish; Bates, Alison
Abstract: Several studies have been performed in the last three decades to assess the impacts of marine biofouling on offshore wind turbines (OWTs) substructures. Marine biofouling generally refers to the settlement and growth of aquatic organisms on human-made structures situated in marine and estuarine environments. OWTs continue to demonstrate significant energy extraction potential and their performance in the ocean is a promising area of research. Most wind turbine installations are in shallow water depths of less than 100 m. At these depths, biofouling can be seen on a large section of cylindrical structures, including mooring lines or power cables, with considerable roughness. This paper provides a review of biofouling phenomena in the context of offshore/marine cylindrical structures. The ecological and social implications of biofouling are reviewed alongside the technical parameters of what is considered to be undesired growth among engineers. The review specifically highlights various marine fouling parameters and laboratory approaches employed by past researchers in modelling biofouling, and the latter's effects on hydrodynamic loading from wave and current excitation. This paper explores challenges in modelling biofouling caused by its intrinsic randomness and uncertainty, as well as suggestions for many studies on marine fouling that are currently absent. Highlights: Study of the effect of surface roughness is done under the premise of hard biofouling. Only a few studies have investigated the impact of soft and lengthy flapping biofouling. Dependence of biofouling only on surface roughness remains a debated topic. Ecological effects of biofouling and social preferences for artificial reefs complicate antifouling designs. Most research rarely considers the effects of fatigue environmental conditions on OWTs substructures.